College students against Sexually Transmitted Infections. An audience study from Health Communication - Montes de Oca, Acianela (2013)
The statistics of the major international health organizations, shows that most affected by sexually transmitted infections (STIs) are young, which also can have consequences that affect the rest of their lives. An audience study to understand how a selected sample of university students construct ideas about these diseases, how these notions are reflected in their sexual practice, and what sources prefer to learn on the subject, reveals that traditional media are no longer within of the main areas in which they obtain information or share ideas about STIs. Neither their schools provide reliable information on the subject. They prefer face-to-face communication, and the Internet and social networks to the extent that allow interactivity and dialogue. They favor a playful perspective as well as practical and useful information.